Anti-IgE and Anti-IL5 Biologic Therapy in the Treatment of Nasal Polyposis: A Systematic Review and Meta-analysis. (November 2017) - Rivero, Alexander; Liang, Jonathan
Objective: To determine the role of biologic therapy on sinonasal symptoms and objective outcomes in chronic rhinosinusitis with nasal polyposis (CRSwNP). Methods: PubMed, OVID MEDLINE, and Cochrane Central were reviewed from 2000 to 2015. Inclusion criteria included English-language studies containing original data on biologic therapy in CRSwNP patients with reported outcome measures. Two investigators independently reviewed all manuscripts and performed quality assessment and quantitative meta-analysis using validated tools. Results: Of 495 abstracts identified, 7 studies fulfilled eligibility: 4 randomized control trials (RCT), 1 case-control, and 2 case series. Outcome measures included nasal polyp score (NPS, 6), computer tomography score (5), and symptom scores (5). Meta-analysis was performed on 5 studies: Anti-IL5 therapy (mepolizumab/reslizumab) and anti-IgE therapy (omalizumab) demonstrated a standard mean difference of NPS improvement of −0.66 (95% CI, −1.24 to −0.08) and −0.75 (95% CI, −1.93 to 0.44), respectively, between biologic therapy and placebo. Quality assessment indicated a low to moderate risk of bias for the RCTs. Conclusion: Biologic therapies may prove beneficial in the treatment of recalcitrant nasal polyposis in select populations. In meta-analysis, anti-IL5 therapy demonstrates a reduction in nasal polyp score. Anti-IgE therapy reduces nasal polyp score in patients with severe comorbid asthma. Additional high-level evidence is needed to assess clinical efficacy.